2007
DOI: 10.1007/s11104-007-9245-1
|View full text |Cite
|
Sign up to set email alerts
|

In-situ phytoextraction of Ni by a native population of Alyssum murale on an ultramafic site (Albania)

Abstract: UltramaWc outcrops are widespread in Albania and host several Ni hyperaccumulators (e.g., Alyssum murale Waldst. & Kit.). A Weld experiment was conducted in Pojske (Eastern Albania), a large ultramaWc area in which native A. murale was cultivated. The experiment consisted in testing the phytoextraction potential of already installed natural vegetation (including A. murale) on crop Welds with or without suitable fertilisation. The area was divided into six 36-m 2 plots, three of which were fertilised in April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 23 publications
6
82
1
2
Order By: Relevance
“…Mazej and Germ (2009) Nickel toxicity levels may vary according to plant species, with toxic levels of nickel in plants ranging from 8 to 147 mg kg -1 (Gupta et al 2008). Sengar et al (2008) stated that, in general, nickel toxicity is expressed when the concentration in plant dry biomass is greater than 50 mg kg -1 , except for accumulating and hyperaccumulating species such as Alyssum murale (9,129 mg kg -1 ) (BANI et al, 2007). Paiva et al (2003) found that in the roots of ipe-purple seedlings, the maximum nickel level reached was 669.1 mg kg -1 at the 190.9 µmol L -1 nickel dose, this being 716% higher than the control treatment.…”
Section: Revmentioning
confidence: 99%
“…Mazej and Germ (2009) Nickel toxicity levels may vary according to plant species, with toxic levels of nickel in plants ranging from 8 to 147 mg kg -1 (Gupta et al 2008). Sengar et al (2008) stated that, in general, nickel toxicity is expressed when the concentration in plant dry biomass is greater than 50 mg kg -1 , except for accumulating and hyperaccumulating species such as Alyssum murale (9,129 mg kg -1 ) (BANI et al, 2007). Paiva et al (2003) found that in the roots of ipe-purple seedlings, the maximum nickel level reached was 669.1 mg kg -1 at the 190.9 µmol L -1 nickel dose, this being 716% higher than the control treatment.…”
Section: Revmentioning
confidence: 99%
“…In relation to the recent molecular, genetic and morphological evidence, from native populations, several species previously regarded as endemic hyperaccumulators can hardly be accepted as separate from A. murale, and we should treated all these taxa as synonyms of the species A. murale (Reeves et al, 2001;Hartvig, 2002;Whiting et al, 2003). A. murale is widespread in the serpentines in the Balkans and its accumulation potential is well documented in Serbia (Tumi et al, 2012) and, in particular, in Albania, Greece and Bulgaria (Bani et al, 2007; Given the importance of A. murale as a potental source for a phytomining and the fact that there are no data on hyperaccumulation characteristic of its native populations in Bosnia and Herzegovina, nor on the soil characteristics over a wide serpentinite area in this region, the aims of this study were: (a) to investigate soil chemical properties from several serpentine sites in central region of Bosnia and Herzegovina on which this species was recorded; (b) to investigate levels of accumulation and translocation of trace metals in plant tissues (roots, stems, and leaves), with a specific focus on Ni; and, (c) to estimate the potential use of local population for phytoextraction.…”
Section: Introductionmentioning
confidence: 99%
“…3, Table 8), such as anisole (entry 16), benzene (entries [13][14][15], chlorobenzene (entries 19-21), 1,4-dimethylbenzene (entry 17), 1,2-diethylbenzene (entry 18). The reaction was satisfactory with [19][20][21]. The benzylation of 1,4-dimethyl-and 1,2-diethylbenzene were carried out with good yields (entries 17 and 18).…”
Section: Other Electrophilic Aromatic Substitutionsmentioning
confidence: 94%
“…Wide-scale development of phytoremediation requires agronomic skills: previous examples in Saint-Laurent-le-Minier, France showed that metal tolerant species could successfully prevent soil erosion [17]. In the case of nickel, previous studies showed that phytoextraction was possible with yields good enough to foresee commercial applications [18][19][20]. Latest studies on former mine sites in the South of France showed a very interesting potential [10,17] but zinc phytoextraction has not yet been subject to fi eld-scale trials.…”
Section: State Of the Art Methods To Reclaim Metal Contaminated Soilsmentioning
confidence: 99%